JUSTICIA TRANSICIONAL Y DERECHOS HUMANOS EN EL PROCESO DE PAZ DE EL SALVADOR: DEUDAS A LAS VÍCTIMAS 26 AÑOS DESPUÉS (2016)
The article evaluates the protection of human rights faced by victims of the armed conflict in El Salvador after the signing of peace. At the beginning an evolution of the previous pacts that would give the political and legal framework for the signing of the Chapultepec in 1992. This was signed by the FMLN guerrillas and the Government of El Salvador after eight years of negotiations is presented and ended civil war that left more than 75,000 murders. The core of the article follows the approval of the amnesty laws that ignore key elements entered into agreements aimed to eradicate impunity. Finally, 26 years after it implemented a model for Transitional Justice The state has been faced international demands that denote the breach made the victims of the conflict. In addition, there continue to be the date internal complaint that show how the center of the pacification of the nation was the victimizer, leaving aside compensation to victims.